The Resource-Based View: A Review and Assessment of Its Critiques - Kraaijenbrink, Jeroen; Spender, J.-C.; Groen, Aard J. (Journal of Management, 2010)
The resource-based view (RBV) of the firm has been around for over 20 years—during which time it has been both widely taken up and subjected to considerable criticism. The authors review and assess the principal critiques evident in the literature, arguing they fall into eight categories. They conclude the RBV’s core message can withstand criticism from five of these quite well provided the RBV’s variables, boundaries, and applicability are adequately specified. Three critiques that cannot be readily dismissed call for further theorizing and research. They arise from the indeterminate nature of two of the RBV’s basic concepts—resource and value—and the narrow conceptualization of a firm’s competitive advantage. As their suggestions for this work indicate, the authors feel the RBV community has clung to an inappropriately narrow neoclassical economic rationality, thereby diminishing its opportunities for progress. The authors’ suggestions may assist with developing the RBV into a more viable theory of competitive advantage, especially if it is moved into a genuinely dynamic framework.